Nutrients and Phytochemical Composition of three Commonly Consumed Local Dish in Ohaji Egbema Local Government, Imo State (IPS Journal of Nutrition and Food Science, 2025)
Background: Nutrient and phytochemical analysis plays a crucial role in understanding the nutritional composition and potential health benefits of traditional dishes.Aim: The nutritional and phytochemical properties of three commonly consumed local dishes in Ohaji Egbema Local Government Area, Imo State, were investigated.Materials and Methods: Three samples were analyzed: oha soup with eba, ukazi soup with fufu, and ugba. The samples were examined for mineral content (calcium, iodine, and iron), vitamins (Vitamin A, C, and E), phytochemicals (lignans, flavonoids, and phytoestrogens), and proximate composition (moisture, carbohydrate, fat, protein, crude fiber, and ash) using standard analytical methods.Results: The highest and lowest vitamin C levels were recorded in oha soup with eba (97.70±4.67 mg/100 g) and ukazi soup with fufu (28.40±2.26 mg/100 g), respectively (p
Keywords: Nutrients; Phytochemical; Local Dishes; Oha soup; Ukazi; Ugba; Flavonoids